2011
DOI: 10.4028/www.scientific.net/amm.148-149.736
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Two Surfaces in Line Contact under TEHL with Non-Newtonian Lubricants

Abstract: This paper presents the static characteristics of two surfaces in line contact under TEHL with non-Newtonian lubricant. Modified Reynolds equation, elastic equation and energy equation were formulated to obtain the model. The model was simulated based on numerical method by using Newton-Raphson and multigrid multilevel techniques. The static characteristics of the two surfaces in line contact under TEHL such as film pressure, film thickness and film temperature profiles in the contact region were examined at v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Murched, Leong and Yang [8] founded that the effective thermal conductivity and viscosity of nanofluids were found to significantly increase with the particle volume fraction. Rattapasakorn and Mongkolwongrojn [9] showed a behavior of thin film lubricant with focusing on temperature effect of contact surface. It is found that the film pressure increase but film thickness decrease due to the temperature in the contact regime under TEHL.…”
Section: Introductionmentioning
confidence: 99%
“…Murched, Leong and Yang [8] founded that the effective thermal conductivity and viscosity of nanofluids were found to significantly increase with the particle volume fraction. Rattapasakorn and Mongkolwongrojn [9] showed a behavior of thin film lubricant with focusing on temperature effect of contact surface. It is found that the film pressure increase but film thickness decrease due to the temperature in the contact regime under TEHL.…”
Section: Introductionmentioning
confidence: 99%